Uma perspectiva teórica sobre a formação acadêmico-profissional dos discentes do curso de Relações Públicas - Silva, Vivian França da (Brasil, 2023)
This research aims to analyze the theoretical perspective on the academic-professional training of undergraduate students in public relations for the development of skills, based on the scientific publications of the Annals of Brazilian Scientific Congresses on Organizational Communication and Public Relations, promoted by the Brazilian Association of Organizational Communication and Public Relations Researchers (Abrapcorp), and the Regional and National Congresses of Communication Sciences, held by the Brazilian Society of Interdisciplinary Communication Studies (Intercom), from 2018 to 2021. research identified two (2) publications in the 2018 National Intercom Congress proceedings, and nine (9) in the Abrapcorp Congress proceedings, with 2019 being the year with the highest number of publications, and 2020 the lowest number of articles. Finally, it was concluded that it is necessary to create strategies for teacher training in the field of public relations. In addition, it is necessary to discuss the guidelines set out in the new National Curriculum Guidelines (MEC, 2013) for public relations courses to rethink the elaboration of a curriculum proposal that is more appropriate to the student's reality. Finally, encouraging the production of research on learning in public relations can contribute to promoting improvements in courses in the area.